PROJECT BASED ACTIVITIES IN A CALL CLASSROOM: EFL STUDENTS’ EXPERIENCES - Gai Mali, Yustinus Calvin; Timotius, Anne Indrayanti (International Journal of Education, 2018)
This study investigates students’ perspectives and measured their attitude, confidence, and anxiety when interacting with omputer Assisted Language Learning (CALL) through project-based instructions. Thirty students from a CALL course participated in this study by responding to a questionnaire and writing a reflective note about their experiences in the course. The qualitative research findings indicate that the majority of the students possess a ositive attitude, confidence and anxiety levels towards the use of technology in their course even though the statistical analysis indicated that there were no significant differences of the students’ attitudes, confidence, and anxiety levels before and after taking the CALL course. Considering the findings, the researchers suggest hat the technology-based projects discussed in the present study can become viable learning activities to prepare pre-service EFL teachers to deal with the effort and initiative by the Ministry of Education in some countries to encourage local teachers integrating the best and wisest use of technology into lessons. Pedagogical implications for teaching and learning CALL as well as direction for further research are discussed in the study.